Colonial Roots Exposed: Tracking the Paradigmatic and Discursive Shifts of the Canadian Institutional Mother-Child Program - Grégoire, Alyssa (Université d'Ottawa / University of Ottawa, 2022)
Despite the increasing numbers of criminalized women in Canada, the use of the Institutional Mother-Child Program (MCP) remains low (Brennan, 2014). It is well known in fields of Criminology, Criminal Justice, and Indigenous Studies, that Indigenous Peoples are overrepresented in Canadian prisons; they represent about five percent of the overall Canadian population, however Indigenous women make up forty percent of all incarcerated women (Miller, 2017). Incarcerated Indigenous women are often mothers of young children, come from poor backgrounds, have little education, and suffered abuse at some point during their lives (Monchalin, 2016). In this thesis, using Indigenous Feminisms (IF) (Suzack, 2010, 2015) and Penal Moderation (Loader, 2010; Snacken, 2015), I address the following research questions: How has the MCP policy evolved over time? How have the policy changes represented a (de)colonial approach to criminal justice policy? To answer these questions, I conducted a feminist critical discourse analysis (FCDA) of all the final versions of the Correctional Service of Canada’s MCP policy (CD 768).
Keywords: Mother-Child Program; Prison nurseries; Incarcerated Mothers; Children in Prison; Mothering in Prison; Colonialism; Indigenous Feminisms; Penal Moderation; Feminist Critical Discourse Analysis